2023
DOI: 10.3389/fnagi.2023.1186681
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the current status of rehabilitation motivation and its influencing factors in older adults with stroke: a cross-sectional study

Abstract: ObjectiveAmong stroke patients, exercise adherence is an important factor in reducing the rate of physical disability and mortality. Rehabilitation exercise after stroke is a safe and effective measure to restore normal body functions, but the analysis of factors influencing patients’ motivation for rehabilitation is not well established. Therefore, this study will explore the influencing factors of rehabilitation motivation in older adults with stroke so as to reduce the disability rate of stroke.MethodA conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…In terms of cognitive function ( Figure 1D ), MMSE assessment showed that 38.83% ( 22 ) of participants had mild cognitive impairments, while the rest were normal. Regarding emotional aspects, only 0.97% ( 14 ) of patients were likely to have depression ( Figure 1A ), and 27.18% ( 23 ) of patients were likely to have anxiety ( Figure 1B ), with no participants exhibiting severe depression (>35 points) or severe anxiety (>29 points). According to the AES-C, 42.72% ( 24 ) of participants had scores ≥35, indicating possible clinical signs of apathy ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of cognitive function ( Figure 1D ), MMSE assessment showed that 38.83% ( 22 ) of participants had mild cognitive impairments, while the rest were normal. Regarding emotional aspects, only 0.97% ( 14 ) of patients were likely to have depression ( Figure 1A ), and 27.18% ( 23 ) of patients were likely to have anxiety ( Figure 1B ), with no participants exhibiting severe depression (>35 points) or severe anxiety (>29 points). According to the AES-C, 42.72% ( 24 ) of participants had scores ≥35, indicating possible clinical signs of apathy ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Например, в работе M. Tan и соавт. [28] показано, что снижение мотивации и функциональных функций у больных связано со страхом перед физическими нагрузками.…”
Section: Discussionunclassified
“…Therapists need to devise training methods that are easy to continue, and the participants’ motivation and subjective evaluation of the training should also be considered. Motivation for rehabilitation has been shown to play a dominant role in the rehabilitation process and promotes a reduction in the rate of disability [ 28 ]. Therefore, a subjective evaluation was conducted to establish whether the DS exercises were easy to adhere to for healthy participants.…”
Section: Methodsmentioning
confidence: 99%